Sleep and Epilepsy Syndromes - Schmitt, Bernhard (Neuropediatrics, 2015)
Sleep and epilepsy have a close relationship. About 20% of patients suffer seizures only during the night, approximately 40% only during the day and approximately 35% during the day and night. In certain epilepsy syndromes, the occurrence of seizures is strongly related to sleep or awakening. Infantile spasms appear predominately on awakening, and hypsarrhythmia is sometimes visible only in sleep. Children with Panayiotopoulos syndrome or benign epilepsy with centrotemporal spikes (BECTS) have seizures mostly when asleep, and in both syndromes interictal spike waves are markedly accentuated in slow wave sleep. Electrical status epilepticus during slow sleep/continuous spike wave discharges during sleep (ESES/CSWS), atypical benign partial epilepsy, and Landau–Kleffner syndrome are epileptic encephalopathies with substantial behavioral and cognitive deficits, various seizures, and continuous spike–wave activity during non–rapid eye movement (NREM) sleep. The hallmark of juvenile myoclonic epilepsy and grand mal seizures on awakening are seizure symptoms within 2 hours after awakening, often provoked by sleep deprivation. Nocturnal frontal lobe epilepsy is sometimes mistaken for parasomnia. Differentiation is possible when the clinical symptoms and the frequency of the paroxysmal events per night and month are carefully observed and nocturnal video electroencephalography (EEG) performed. Sleep EEG recordings may be helpful in patients with suspected epilepsy and nonconclusive awake EEG. Depending on the clinical question, sleep recordings should be performed during nap (natural sleep or drug induced), during the night, or after sleep deprivation.
Keywords: sleep; epileptic encephalopathy; benign childhood focal epilepsies; juvenile myoclonic epilepsy; frontal lobe epilepsy; parasomnias